LEAP2 deletion in mice enhances ghrelin's actions as an orexigen and growth hormone secretagogue - Kripa Shankar; Nathan P. Metzger; Omprakash Singh; Bharath K. Mani; Sherri Osborne-Lawrence; Salil Varshney; Deepali Gupta; Sean B. Ogden; Shota Takemi; Corine P. Richard; Karabi Nandy; Chen Liu; et al. (Elsevier, 2021)
Objective: The hormone liver-expressed antimicrobial peptide-2 (LEAP2) is a recently identified antagonist and an inverse agonist of the growth hormone secretagogue receptor (GHSR). GHSR's other well-known endogenous ligand, acyl-ghrelin, increases food intake, body weight, and GH secretion and is lowered in obesity but elevated upon fasting. In contrast, LEAP2 reduces acyl-ghrelin-induced food intake and GH secretion and is found elevated in obesity but lowered upon fasting. Thus, the plasma LEAP2/acyl-ghrelin molar ratio could be a key determinant modulating GHSR signaling in response to changes in body mass and feeding status. In particular, LEAP2 may serve to dampen acyl-ghrelin action in the setting of obesity, which is associated with ghrelin resistance. Here, we sought to determine the metabolic effects of genetic LEAP2 deletion. Methods: We generated the first known LEAP2-KO mouse line. Food intake, GH secretion, and cellular activation (c-fos induction) in different brain regions following s.c. acyl-ghrelin administration in LEAP2-KO mice and wild-type littermates were determined. LEAP2-KO mice and wild-type littermates were submitted to a battery of tests (such as measurements of body weight, food intake, and body composition; indirect calorimetry, determination of locomotor activity, and meal patterning while housed in metabolic cages) over the course of 16 weeks of high-fat diet and/or standard chow feeding. Fat accumulation was assessed in hematoxylin & eosin-stained and oil red O-stained liver sections from these mice. Results: LEAP2-KO mice were more sensitive to s.c. ghrelin. In particular, acyl-ghrelin acutely stimulated food intake at a dose of 0.5 mg/kg BW in standard chow-fed LEAP2-KO mice while a 2× higher dose was required by wild-type littermates. Also, acyl-ghrelin stimulated food intake at a dose of 1 mg/kg BW in high-fat diet-fed LEAP2-KO mice while not even a 10× higher dose was effective in wild-type littermates. Acyl-ghrelin induced a 90.9% higher plasma GH level and 77.2-119.7% higher numbers of c-fos-immunoreactive cells in the arcuate nucleus and olfactory bulb, respectively, in LEAP2-KO mice than in wild-type littermates. LEAP2 deletion raised body weight (by 15.0%), food intake (by 18.4%), lean mass (by 6.1%), hepatic fat (by 42.1%), and body length (by 1.7%) in females on long-term high-fat diet as compared to wild-type littermates. After only 4 weeks on the high-fat diet, female LEAP2-KO mice exhibited lower O2 consumption (by 13%), heat production (by 9.5%), and locomotor activity (by 49%) than by wild-type littermates during the first part of the dark period. These genotype-dependent differences were not observed in high-fat diet-exposed males or female and male mice exposed for long term to standard chow diet. Conclusions: LEAP2 deletion sensitizes lean and obese mice to the acute effects of administered acyl-ghrelin on food intake and GH secretion. LEAP2 deletion increases body weight in females chronically fed a high-fat diet as a result of lowered energy expenditure, reduced locomotor activity, and increased food intake. Furthermore, in female mice, LEAP2 deletion increases body length and exaggerates the hepatic fat accumulation normally associated with chronic high-fat diet feeding.